Analisis Kesukaan Fillet Ikan Gabus Sambal Tempoyak dalam Kemasan Standing Pouch Solusi di Era Pandemi - Selly Ratna Sari; Elmeizy Arafah; Guttifera Guttifera (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Arafah, E, Sari R, Guttifera G. 2021. Snakehead fish tempoyak sauce fillets in standing pouch packaging solution in era pandemic. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 884-890. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Tempoyak is local product from South Sumatera made from fermented durian. Snakehead fish tempoyak sauce is a diversification product that available throughout the year. Snakehead fish tempoyak sauce in packaging pouch could be a choice as typical souvenir from South Sumatera and at the same time support Food for Tourism program or even as alternative souvenir from Palembang and solution in era pandemic. This study aimed to found the greatest formula between tempoyak and condiment to produce prefer and nutritious e.g. protein of tempoyak sauce. This study used different treatment for the amount of tempoyak i.e. A) A1 = 40 g, A2 = 50 g and A3 = 60 g. Different amount of condiment i.e. (B): B1= 100 g B2= 200 g and B3= 300 g. The organoleptic properties analysis such as appearance, texture and taste were determined. All the treatments were not statistically significant. Whereas, taste panelis testing result indicated both like and very like. The result showed that A3B2 combination with 60 g tempoyak dan 300 g condiment was the greatest treatment. So then, snakehead fillet tempoyak sauce was accepted by panelis.